An annotated interview with Beastwars: Language, identity and place in New Zealand metal - Kruk, Jessica; Robertson, Wesley C (Perfect Beat, 2023)
In 2021, we interviewed Matt Hyde of Wellington’s Beastwars for our ethnographic podcast Lingua Brutallica as part of a project exploring language in metal scenes outside of America and Europe. In this annotated interview, we edit, discuss and frame the content of the interview in relation to how Hyde’s comments shed light on important conflicts between personal, local and global understandings of what makes ‘metal’ lyrics and music. The interview covers, in Hyde’s own words, his approach to metal lyrics, and how he weaves his personal experiences and New Zealand’s unique landscape into images of pagan rituals, ancient battles, death, and other emblems of international ‘metal’ practices. This distinctive taste of New Zealand metal that results brings together the local and international scenes that devour it. Through breaking up the transcript with commentary on the sociolinguistic insights Hyde provides on understandings of language, metal and identity, we explore how Hyde aligns with, resists, and feels pressured by stereotypes of ‘metal language’, producing a guided tour of how a key figure in New Zealand metal has navigated the fluidity of ‘local’ and ‘global’ language practice in metal music throughout his 15 years in the scene.